L’ancrage au quotidien dans les colonies populaires de la périphérie de Mexico : une approche par les pratiques et les ressources du quartier - Jean-François Valette (EchoGéo)
Within the illegal urban settlements, called colonias populares, on the outskirts of Mexico City, the population’s anchorage does not seem obvious. This notion examines the circulation of individuals and their families in the different spatial and temporal scales of the living space. The analysis of the connections between people and their neighborhood highlights the role of residential context as a place of resources. From an empirical work and official surveys analysis, this paper aims to identify the different configurations of the places system on which inhabitants anchorages are built within the city. First, the links to their neighborhood in terms of practices allow to understand the space used in order to access to urban resources. Then, economic and social functionalization of the area is highlighted. In the end, crossing different practices of local and metropolitan areas allows the discovery of several types of links within the neighborhood and a variety of anchorages that fit into these places. Thus, the daily mobility underlines the urban resources existence, but also a relative intensity of movements on other scales, highlighting an integration process with the rest of the city.